An innovative approach to food security policy in developing countries - Katarzyna T. Boratyńska; Raqif Tofiq Huseynov (Journal of Innovation & Knowledge (JIK), 2017)
The article describes and analyzes the innovative concept of food security policy and presents theoretical microeconomic model of food security by Abdulai (2000) that explains individuals' demand for food ingredients. The literature review involves both direct and indirect policy measures that ensure food security in developing countries. These policies involve direct interventions involving structural changes in relative prices and targeted food subsidies, and indirect measures such as improving agricultural infrastructure, the general economic environment, and providing farmers with new farm technologies to increase food production. The manuscript shows the efforts several food security policy researchers have put to examine policy options and their impacts on food security.
Keywords: F63; O11; O12; O13; Q18; 650; Innovativeness; Food security model; Developing countries